Map-matching poor-quality GPS data in urban environments: the pgMapMatch package - Millard-Ball, Adam; Hampshire, Robert C.; Weinberger, Rachel R. (Transportation planning and technology, 2019)
Global Positioning System (GPS) data have become ubiquitous in many areas of transportation planning and research. The usefulness of GPS data often depends on the points being matched to the true sequence of edges on the underlying street network - a process known as 'map matching.' This paper presents a new map-matching algorithm that is designed for use with poor-quality GPS traces in urban environments, where drivers may circle for parking and GPS quality may be affected by underground parking and tall buildings. The paper is accompanied by open-source Python code that is designed to work with a PostGIS spatial database. In a test dataset that includes many poor-quality traces, our new algorithm accurately matches about one-third more traces than a widely available alternative. Our algorithm also provides a 'match score' that evaluates the likelihood that the match for an individual trace is correct, reducing the need for manual inspection.